Fish and fisheries of Periyar Lake, Kerala - Kurup, B Madhusoodana; Kumar, T G Manoj; Radhakrishnan, K V (Indian Journal of Fisheries, 2011)
Periyar tiger reserve is one of the 21 biodiversity hotspots of India. Of the 36fish species collected and identified, 6 are endemic to this biosphere. Whileevaluating them as per IUCN categorization, 7 belonged to criticallyÂ endangeredcategory, 6 are endangered and 8 are vulnerable. Gonoprktopterus micropogonperiyarensis, Lepidopygopsis typus, Crossocheilus periyarensis, Garraperiyarensis, Nemacheilus periyarensis and Nemacheilus menoni are theÂ endemicfish species. On an average 2.3 tonnes of fishes are harvested from the lake,mostly by gill and cast nets, the former contributes to 53.25% while the latter46.75%. During 2001-02, Cyprinus carpio, an exotic species formed 48% of thelandings while Tor khudree accounted for 29% whereas in 2002-03, thecontribution of the former raised to 56% with a reciprocal reduction of the latterto 26%. The percentage contribution of Oreochromis mossambicus was 11 and10% during 2001-02 and 2002-03 respectively. Catch per unit effort (kg/hr) of C.carpio (5.18) and O.mossambicus (3.37) was high compared to the indigenousspecies like T.khudree (3.34) and G.curmuca (2). Length frequency studiesrevealed that C. carpio was dominated by 30-40cm size class while it was 10-20cm in O.mossambicus. In T.khudree 30-40cm was the dominant group and20-30cm in G.curmuca. The threats from the invasion of exotics on the indigenousfish diversity of Periyar tiger reserveÂ has been discussed.